LAPORAN KASUS: PERAN KOLABORATIF PSIKIATRI DALAM TATALAKSANA GANGGUAN PSIKIATRIK PADA PENDERITA MIASTENIA GRAVIS - KAPITA, RAMBU K. B. F.; WAHYUNI, A A SRI; DINIARI, N K SRI; ARYANI, L N ALIT; ARIMBAWA, I KOMANG (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Myasthenia Gravis (MG) is an autoimmune disorder affecting the neuromuscular junction, leading to impaired muscle contraction that worsens with activity and improves with rest. It commonly affects bulbar and skeletal muscles, severely impairing the patient's ability to perform daily activities and requiring long-term therapy. The chronic nature of the disease can lead to psychiatric disorders, which may exacerbate MG symptoms, and vice versa. Psychiatric disorders in this context are not merely psychological responses to the disease but can also be biologically explained. This case report discusses the role of psychiatry in managing psychiatric disorders in MG patients, focusing on measurable therapy outcomes using the quality of life instrument MG-ADL (Myasthenia Gravis Activities of Daily Living), compared with psychiatric disorders such as depression and anxiety using the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). The case involves a 31-year-old female patient with a severe MG crisis, presenting with psychiatric disorders such as depression and anxiety, which were managed through an integrated approach between psychiatry and medical MG management. The use of MG-ADL as a clinical measure showed significant improvement in the patient’s daily functioning following neurological interventions, including definitive MG therapy and psychiatric adjunctive care. Furthermore, BDI and BAI results indicated a significant reduction in scores, correlating with the improvement in MG condition, as monitored through MG-ADL. This case study highlights the importance of collaborative roles between psychiatry and other specialists in managing MG. This collaboration leads to better physical and psychological functioning. The implications of this case report strengthen the argument for a holistic approach to MG management, where psychiatric aspects should not be neglected in efforts to achieve optimal therapeutic outcomes. ABSTRAKMiastenia gravis merupakan gangguan autoimun pada neuromuscular junction menyebabkan gangguan kontraksi otot yang semakin parah dengan aktivitas dan membaik dengan istirahat, sering terjadi pada otot bulbar dan gerak, serta menyulitkan penderita dalam berbagai aspek aktivitas keseharian dan membutuhkan terapi jangka waktu lama. Kondisi penyakit kronis dapat menimbulkan suatu gangguan psikiatri dimana kehadirannya dapat memperparah kondisi MG demikian sebaliknya. Kehadiran Gangguan psikiatrik bukan sebagai suatu respon psikologik semata dalam menghadapi penyakit, melainkan dapat dijelaskan secara biologik. Laporan kasus ini mengulas peran psikiatri dalam manajemen gangguan psikiatri pada pasien MG, dengan fokus pada peningkatan hasil terapi yang terukur menggunakan kualitas hidup dengan instrument MG-ADL (Myasthenia Gravis Activities of Daily Living) dibandingkan dengan gangguan psikiatrik berupa depresi dan kecemasan menggunakan instrument BDI (Beck Depression Inventory) dan BAI (Beck Anxiety Inventory). Kasus melibatkan seorang pasien wanita 31 tahun, dengan krisis MG (gejala berat) yang mengalami gangguan psikiatri seperti depresi dan kecemasan, yang diatasi dengan pendekatan terintegrasi antara psikiatri dan manajemen medis MG. Penggunaan MG-ADL sebagai pengukur klinis menunjukkan perbaikan signifikan dalam fungsi harian pasien setelah intervensi neurologis yaitu terapi definitif MG dan adjuvan psikiatri dilakukan. Selain itu, hasil BDI dan BAI menunjukkan penurunan skor yang signifikan sejalan dengan perbaikan kondisi MG yang terpantau dengan MG-ADL. Studi kasus ini menyoroti pentingnya peran kolaboratif antara psikiatri dan spesialisi lainnya dalam menangani MG. Hal ini mengarah pada perbaikan fungsi fisik dan psikologis yang lebih baik. Implikasi dari laporan kasus ini memperkuat argumen untuk pendekatan holistik dalam manajemen pasien MG, di mana aspek psikiatri tidak boleh diabaikan dalam upaya mencapai hasil terapi yang optimal.